Current emotion research in social psychology: thinking about emotions and other people - Parkinson, B; Manstead, A (SAGE Publications, 2015)
This article discusses contemporary social psychological approaches to (a) the social relations and appraisals associated with specific emotions; (b) other people’s impact on appraisal processes; (c) effects of emotion on other people; and (d) interpersonal emotion regulation. We argue that single-minded cognitive perspectives restrict our understanding of interpersonal and group-related emotional processes, and that new methodologies addressing real-time interpersonal and group processes present promising opportunities for future progress.